Attention and memory after COVID-19 as measured by neuropsychological tests: Systematic review and meta-analysis - Boris B. Velichkovsky; Anna Yu. Razvaliaeva; Alena A. Khlebnikova; Piruza A. Manukyan; Vladimir N. Kasatkin (Acta Psychologica, 2023)
COVID-19 is associated with a range of sequelae, including cognitive dysfunctions as long-standing symptoms. Considering that the number of people infected worldwide keeps growing, it is important to understand specific domains of impairments to further organize appropriate rehabilitation procedures. In this study we conducted a meta-analysis to investigate specific cognitive functions impacted by COVID-19. A literature search was conducted in Web of Science, Scopus, PubMed, Academic Search Premier, Health Source: Nursing/Academic Edition, and preprint databases (OSF and PsyArXiv via OSF Preprints, medRxiv, bioRxiv, Research Square). We included the studies that compared cognitive functioning in COVID-19 reconvalescents and healthy controls, and used at least one validated neuropsychological test. Our findings show that short-term memory in the verbal domain, and possibly, visual short-term memory and attention, are at risk in COVID-19 reconvalescents. The impact of COVID-19 on cognitive functioning has yet to be studied in detail. In the future more controlled studies with validated computerized tests might help deepen our understanding of the issue. PsycINFO classification: 3360 Health Psychology & Medicine